Literacy artifacts and the semiotic landscape of a spanish secondary school. - Poveda, David (Reading Research QuarterlyReading Research Quarterly, 2012)
In this article, author examines literacy artifacts placed by students in different locations of a state-run secondary school in the city of Madird. The analysis draws from concepts developed in semiotics, linguistics anthropology, literacy studies, and social geography.
Keywords: enseignement; jeunesse; linguistique; literacy; sémiotique